TOTAL COLONIC AGANGLIONOSIS: DILEMA DIAGNOSIS DAN DAMPAK JANGKA PANJANG - Qisthinadia Hazhiyah Setiadi (Unram Medical Journal, 2021)
Total colonicic aganglionosis (TCA) is a rare variant of Hirschsprung (HSCR). It occurs in approximately 2% -13% of the cases. Diagnosis TCA is challenging. Total colonic aganglionosis appears to represent a different clinical manifestation from other types of HSCR, both from clinical, radiologic, and histologic aspect. The underlying pathophysiologic is also thought to be due to a number of pathophysiologic mechanisms that differ from other types of HSCR. It is not yet clear whether TCA merely represents a long form of HSCR or a different expression of other disease. In addition, the complication and long term outcome after surgery are also a challenge. Over the last several decades, improvements in the post operative care have led to lower mortality rate, which is now less than 5%. However, morbidity remained significant. The problem in TCA is not about its operative management, but lies in the accuracy of diagnosis and management of complication after surgery. Improvements in supportive care especially after surgery, early detection, and proper treatment have led to the increased rate of survival in TCA.